Investigating links between Internet literacy, Internet use, and Internet addiction among Chinese youth and adolescents in the digital age - Jiang, Qiaolei; Chen, Zonghai; Zhang, Zizhong; Zuo, Can (Frontiers in Psychiatry, 2023)
In current digital era, adolescents’ Internet use has increased exponentially, with the Internet playing a more and more important role in their education and entertainment. However, due to the ongoing cognitive, emotion, and social development processes, youth and adolescents are more vulnerable to Internet addiction. Attention has been paid to the increased use of Internet during the COVID-19 pandemic and the influence of Internet literacy in prevention and intervention of Internet addiction. The present study proposes a conceptual model to investigate the links between Internet literacy, Internet use of different purpose and duration, and Internet addiction among Chinese youth and adolescents. In this study, N = 2,276 adolescents studying in primary and secondary schools in East China were recruited, and they completed self-reports on sociodemographic characteristics, Internet literacy scale, Internet use, and Internet addiction scale. The results showed a significant relationship between Internet use and Internet addiction. To be specific, the duration of Internet use significantly and positively affected Internet addiction. With different dimensions of Internet literacy required, entertainment-oriented Internet use had positive impact on Internet addiction, while education-oriented Internet use exerted negative effects on Internet addiction. As for Internet literacy, knowledge and skills for Internet (positively) and Internet self-management (negatively) significantly influenced the likelihood of Internet addiction. The findings suggest that Internet overuse increases the risk of Internet addiction in youth and adolescents, while entertainment-oriented rather than education-oriented Internet use is addictive. The role of Internet literacy is complicated, with critical Internet literacy preventing the development of Internet addiction among youth and adolescents, while functional Internet literacy increasing the risk.